Effect of age at puberty on risk of multiple sclerosis: A mendelian randomization study. (16th April 2019) - Harroud, Adil; Morris, John A.; Forgetta, Vincenzo; Mitchell, Ruth; Smith, George Davey; Sawcer, Stephen J.; Richards, J. Brent
Abstract : Objective: To investigate the potential for a causal effect of age at puberty on multiple sclerosis (MS) susceptibility using a mendelian randomization (MR) approach. Methods: We used 372 genetic variants strongly associated with age at menarche in a genome-wide association study (GWAS) involving 329, 245 women. The genetic architecture of pubertal timing across both sexes is highly correlated (genetic correlation [ r g ] = 0.75, p = 1.2 × 10 −79 ), allowing these variants to provide reliable insight into pubertal timing in males as well. The effect of pubertal timing on risk of MS was measured with summary statistics from a GWAS of 14, 802 cases with MS and 26, 703 controls from the International Multiple Sclerosis Genetics Consortium. Multivariable MR controlling for effects of body mass index (BMI) using genetic data from additional consortia investigated whether pubertal effects on MS were dependent on weight status. Results: A 1-year increase in genetically predicted age at puberty decreased odds of MS by 8% (odds ratio [OR] 0.92, 95% confidence interval [CI] 0.86–0.99, p = 0.03). However, multivariable MR analysis showed that after accounting for effects on adult BMI, the association of age at puberty with MS susceptibility attenuated (OR 0.96, 95% CI 0.88–1.04, p = 0.36). Similar results were obtained when childhood BMI was incorporated. Sensitivity analyses provided no evidence of major bias from genetic pleiotropy. Conclusions: We found support for an association between higher age at puberty and decreased risk of MS with a magnitude comparable to that reported in observational studies. This effect appears to be largely mediated by the strong association between age at puberty and obesity. A large causal effect of pubertal timing independent of BMI is unlikely.